The Pacman Song Meaning Interpreted through Semiotics Analysis - Nuryanti, Dewi; Pragita, Salca (International Journal of Culture and Art Studies, 2023)
This study aimed to interpret the meaning of the song lyrics “Pacman” by EAJ. It used the semiotic analysis by Michael Riffaterre. The research was qualitative descriptive research. Data for the research was the lyrics of the Pacman song by EAJ. The research found that the heuristic reading process in the “Pacman” lyrics still discussed each line’s meaning. It was interpreted when a person loved someone and would give anything and did anything even if it ended painfully as long as he/she was together with his/her mate. Then “Pacman and Lover” was analyzed as a model. “Cause my head says no, but my phone keeps calling you.” and “Over and Over, like it’s Red Rover” was analyzed as a variant. “People who love to die for someone” was analyzed as a matrix. Last, “one-sided love” was explored as a potential hypogram, and “Pacman” was analyzed as an actual hypogram. This research concludes that the hidden meaning of “Pacman” lyrics is when a person loves someone deeply. Even if a loved one hurts him, he will still love his lover.